Assessment of rhinological parameters for evaluating the effects of airborne irritants to the nasal epithelium - Klimek, Ludger; Hundorf, Inga; Delank, K.-Wolfgang; Hörmann, Karl (International archives of occupational and environmental health, 2002)
Objectives: The initial contact area of inhaled toxins with the human body is the nasal mucosa. Upon irritation, nasal symptoms may occur that are well known as common viral infections of the airway and thus neglected by patients and physicians. Therefore, objective methods should be used to determine even minor irritative or inflammatory changes. Methods: Objective methods to assess changes in the nasal epithelium include endoscopy, rhinomanometry, acoustic rhinometry, anemometry, thermometry, laser Doppler flowmetry, measurements of mucociliary transport time and ciliary beat frequency, analysis of nasal secretions, nasal cytology, and subjective (UPSIT, CCCRC, Sniffin Sticks) and objective (electro-olfactogram, olfactory event related potentials) and olfaction tests. Results: Several different inhaled irritative and toxic substances, including metal dusts and steam, volatile organic substances, and inorganic gases, may harm the nasal epithelium. Conclusions: The objective evaluation of nasal functions should be used to assess effects of airborne irritants. For patients complaining of toxic effects, early diagnosis is important in the prevention of severe damage to the upper and lower airways.